The Use of Telehealth to Enhance Care in ALS and other Neuromuscular Disorders. Issue 6 (16th April 2020) - Haulman, Anne; Geronimo, Andrew; Chahwala, Amit; Simmons, Zachary
Abstract: Telehealth has the potential to improve the efficiency of healthcare while reducing the burden on patients and caregivers. Encounters can be synchronous or asynchronous. When used for care of those with amyotrophic lateral sclerosis (ALS) by individual health care providers or by a multidisciplinary team, synchronous telehealth is feasible, acceptable, may produce outcomes comparable to those of in‐person care, and is cost effective. Individuals with ALS who use telehealth tend to have lower physical and respiratory function and to live farther from an ALS clinic than those who exclusively attend in‐person clinic visits. Asynchronous telehealth can be used as a substitute full multidisciplinary visits, or for remote monitoring of pulmonary function, gait/falls, and speech. Barriers to implementing telehealth on a wider scale include disparities in access to technology and challenges surrounding medical licensure and billing, but these are being addressed.